Air infiltration: a key issue on household refrigerators - Clito F. Afonso (2008)
One important vector for a sustainable growth of our planet is the airventilation due to the large amounts of energy spent. When speaking aboutventilation, the main thought is concerned with buildings. However, there is onemore important sector, besides the building one, where a special attention is due:the refrigeration sector. The cooling of the outside air due to the air infiltration onrefrigeration stores can consume also a large amount of energy. Read these notescarefully all the way through and follow them as precisely as possible. In this workseveral measurements were carried out on a common household refrigerator inorder to find the air exchange rate trough the magnetic seal of the door. Tests wererealized with a new and an old door seal. The main conclusion to withdraw is thatthe air infiltration rate on the refrigerator increases very fast as it becomes old,increasing in that way the energy consumption of the refrigerator.